RETRACTED: Veterinary and sanitary assessment of rabbit meat when using the Zdravur feed additive - Smolentsev Sergey; Naumova Olga; Maksimovich Dina; Zhuravel Nina; Chernyshova Larisa; Semenova Svetlana; Krasovskaia Iuliia; Khasiyatullin Airat; Makaeva Alsu; Shlyamina Oksana (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001